PEMBERIAN HUKUMAN POSITIF GURU BIMBINGAN KONSELING DI SMPN 1 KALASAN YOGYAKARTA - Taslima Taslima (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2018)
AbstractSchool is a formal institution that has an order that must be obeyed. There are various penalties given by the teacher in school so that students do not repeat the same mistakes in the future. Today there are still many educational institutions giving negative penalties. This article examines the positive punishment given by counseling teachers to deal with the indiscipline of students at Kalasan 1 Public Middle School. The purpose of this article is to understand what penalties and types of positive punishment given by the BK teacher to their students. This article concludes that the positive punishment given by counseling tutors at 1 Kalasan Middle School is aimed at training discipline.Keywords: Discipline, punishment, counseling. AbstrakSekolah merupakan lembaga formal yang memiliki tata tertib yang harus dipatuhi. Ada bermacam-macam hukuman yang diberikan oleh guru bk di sekolah agar siswa tidak mengulangi kesalahan yang sama di masa yang akan datang. Sekarang ini masih banyak lembaga pendidikan memberikan hukuman negatif. Artikel ini mengkaji tentang pemberian hukuman positif oleh guru bimbingan konseling untuk menangani ketidakdisiplinan siswa di SMPN 1 Kalasan. Tujuan artikel ini adalah untuk memahami hukuman dan jenis hukuman positif apa saja yang diberikan oleh guru BK kepada siswanya. Artikel ini menyimpulkan bahwa hukuman positif yang diberikan oleh guru bimbingan koseling di SMPN 1 Kalasan, bertujuan untuk melatih kedisiplinan.Kata kunci: Kedisiplinan, hukuman, bimbingan konseling.